Effect of Fruit Maturity Level on Morphology, Water Content and Germination of Eumachia montana Seeds - Lestari, Dewi Ayu; Faya, Ananda Kautsar Nadia; Ismanjani, Lutvinda (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Eumachia montana is one local plant species from Rubiaceae family that has potential as medicinal plant. Seed storage of E. montana depends on seed quality. Seed quality can be determined from fruit harvesting accuracy at physiological maturity through fruit maturity level. The aim of this study was to analyze effect of E. montana fruit maturity level to seed morphology, water content and germination. Fruits were harvested based on maturity level which was grouped based on fruit skin color. E. montana seeds are morphometric characterized, measured for water content and sown. Data were analyzed by variance analysis, Principal Component Analysis, cluster and correlation analysis using statistical program PAST ver. 3.04. Fruit maturity level of E. montana significantly influence to seed morphology and germination, but did not significantly influence to seed water content. Grade III with dark orange (10R 5/10) fruit skin color is recommended as fruit maturity level of E. montana for harvesting. Seed length is parameter of seed morphology which influence to fruit maturity level. Correlation between fruit maturity level to seed morphology, water content and germination is low, with seed morphology character is positively correlated to germination of E. montana seeds.